2001
DOI: 10.1211/0022357011776595
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of prostaglandin E2 production by 2′-hydroxychalcone derivatives and the mechanism of action

Abstract: The effects of 14 synthetic 2'-hydroxychalcone derivatives on prostaglandin E2 (PGE2) production in rat peritoneal macrophages stimulated by the protein kinase C activator, 12-O-tetradecanoylphorbol 13-acetate (TPA), were examined to clarify the structure-activity relationship. 2',4-Dihydroxy-4'-methoxychalcone (compound 3), 2',4-dihydroxy-6'-methoxychalcone (compound 8) and 2'-hydroxy-4'-methoxychalcone (compound 9) suppressed PGE2 production more potently than the other compounds. The IC50 (50% Inhibitory co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Among them, 2 -hydroxyl substituted chalcones have attracted much attention because they can prevent platelet aggregation (Lin et al, 1997), polymixin B-induced edema (Hsieh et al, 1998), LPSinduced septic shock (Batt et al, 1993), and glomerulonephritis (Hayashi et al, 1996) in animal models. 2 -Hydroxychalcone can also suppress the adhesion of activated neutrophils to HUVEC cell cultures (Madan et al, 2000), and its derivatives are inhibitors of TPAinduced COX-2 expression in rat macrophages (Kim et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 2 -hydroxyl substituted chalcones have attracted much attention because they can prevent platelet aggregation (Lin et al, 1997), polymixin B-induced edema (Hsieh et al, 1998), LPSinduced septic shock (Batt et al, 1993), and glomerulonephritis (Hayashi et al, 1996) in animal models. 2 -Hydroxychalcone can also suppress the adhesion of activated neutrophils to HUVEC cell cultures (Madan et al, 2000), and its derivatives are inhibitors of TPAinduced COX-2 expression in rat macrophages (Kim et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The D-A structure,i ntramolecular H-bond with ESIPT nature, slip-packing structure and molecular planarization effectively make the crystals 1-3 highly emissive in the deep red/NIR region. To explore the emission mechanism of crystals 1-3, [10] All the compounds are synthesized according to the literature. [11] We obtained red crystals with centimeter-scale size and slab-like shape based on 1-3.Asshown in Figure 1, the crystals display bright deep red to NIR fluorescence (l em = 680-716 nm; F f = 0.25-0.32), although their solutions are almost non-emissive (F f < 0.01).…”
mentioning
confidence: 99%
“…This compound was initially isolated from the seeds of Amomum subulatum and subsequently from other zingiberous plant species. The SAR studies of chalcones showed that among 2'-hydroxychalcone derivatives a methoxy group at 4' and 6' is essential for the expression of PGE 2 inhibitory activity and substitution of the B ring is not essential for the activity [28]. Cardamonin is active despite the absence of functional group substitution on the B ring, it has a methoxy substitution on the 6' position of A ring.…”
Section: Alpinia Rafflesianamentioning
confidence: 99%